CRISPR/Cas9 knockout of USP18 enhances type I IFN responsiveness and restricts HIV-1 infection in macrophages. Issue 6 (13th February 2018) - Taylor, Jared P; Cash, Melanie N; Santostefano, Katherine E; Nakanishi, Mahito; Terada, Naohiro; Wallet, Mark A
Abstract: The IFN-stimulated gene ubiquitin-specific proteinase 18 ( USP18 ) encodes a protein that negatively regulates T1 IFN signaling via stearic inhibition of JAK1 recruitment to the IFN-α receptor 2 subunit (IFNAR2). Here, we demonstrate that USP18 expression is induced by HIV-1 in a T1 IFN-dependent manner. Experimental depletion of USP18 by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) gene editing results in a significant restriction of HIV-1 replication in an induced pluripotent stem cell (iPSC)-derived macrophage model. In the absence of USP18, macrophages have increased responsiveness to stimulation with T1 IFNs with prolonged phosphorylation of STAT1 and STAT2 and increased expression of IFN-stimulated genes that are key for antiviral responses. Interestingly, HIV-1 requires some signaling through the T1 IFN receptor to replicate efficiently because a neutralizing antibody that inhibits T1 IFN activity reduces HIV-1 replication rate in monocyte-derived macrophages. USP18 induction by HIV-1 tunes the IFN response to optimal levels allowing for efficient transcription from the HIV-1 LTR promoter while minimizing the T1 IFN-induced antiviral response that would otherwise restrict viral replication and spread. Finally, iPSC and CRISPR/Cas9 gene targeting offer a powerful tool to study host factors that regulate innate immune responses. Abstract : USP18 promotes HIV-1 replication by negatively regulating expression of antiviral genes induced by T1 IFN signaling.